Considerations of Religion and Situational Factors, Internal Control on the Occurrency of Fraud Trends: An Experimental Study of the Financial Services Sector in Indonesia - Indah Kartika Sari; Huraira Rifas (JOURNAL OF ISLAMIC ECONOMICS AND BUSSINES ETHICS, 2024)
Financial statement fraud does not only occur in the private sector but can also occur in the government sector in the form of material misrepresentation of financial statements to cover up the actual financial condition by carrying out financial engineering. This study aims to examine religious considerations and situational factors, namely pressure or directives from superiors and internal controls against committing fraud tendencies. Literature reveals that religion plays a dominant role in shaping employees' values in their work. This study used an experimental method on 33 financial institution employees divided into two sessions to see the impact of scenarios. The analysis technique using Analysis of Variances (ANOVA) is used to perform multivariable comparative analysis. The results of empirical testing show that internal control factors have a negative influence on fraudulent behavior, and pressure factors or superior directions have a positive effect on the tendency to commit fraud. Meanwhile, religious considerations have less influence on fraud tendencies.